Nonaqueous electrolyte solution for lithium secondary battery and lithium secondary battery comprising same

By using a nonaqueous electrolyte solution containing a pyridine compound replaced with halogenated benzene in a lithium secondary battery, the problems of electrolyte solution decomposition and membrane damage under high temperature conditions are solved, and the battery performance is improved and the life span is extended.

CN119605015APending Publication Date: 2025-03-11LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380056051.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-12
Filing Date
2023-07-13
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When lithium secondary batteries operate under high temperature conditions, the lithium salt decomposition products in the electrolyte solution lead to membrane damage and battery performance degradation.

Method used

A nonaqueous electrolyte solution containing a pyridine compound replaced with halogenated benzene is used to form a thin and strong film on the electrode, reducing the decomposition reaction of the electrolyte solution and the dissolution of the transition metal.

Benefits of technology

It effectively suppresses the decomposition reaction of electrolyte solution under high temperature conditions, improves electrochemical properties, reduces the gas production amount and resistance increase rate, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005255810780000021
    Figure BDA0005255810780000021
  • Figure BDA0005255810780000041
    Figure BDA0005255810780000041
  • Figure BDA0005255810780000042
    Figure BDA0005255810780000042
Patent Text Reader

Abstract

The present invention relates to a non-aqueous electrolyte solution for a lithium secondary battery, comprising a compound represented by Formula 1, a lithium salt, and an organic solvent; and a lithium secondary battery including the nonaqueous electrolyte solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to Korean Patent Application No. 10-2022-0098826 filed on August 8, 2022 and Korean Patent Application No. 10-2023-0090520 filed on July 12, 2023, the disclosures of which are incorporated herein by reference.

[0002] The present invention relates to a non-aqueous electrolyte solution for a lithium secondary battery and a lithium secondary battery containing the non-aqueous electrolyte solution. Background Art

[0003] Lithium secondary batteries are generally prepared by the following method: a separator is provided between a positive electrode and a negative electrode to form an electrode assembly, and then the electrode assembly is inserted into a battery case, wherein the positive electrode comprises a positive electrode active material formed of a lithium-containing transition metal oxide, and the negative electrode comprises a negative electrode active material capable of storing lithium ions; a non-aqueous electrolyte solution which becomes a lithium ion transmission medium is injected thereinto, and then the battery case is sealed.

[0004] Since lithium secondary batteries can be miniaturized and have high energy density and operating voltage, they are being used in various fields such as mobile devices, electronic products, and electric vehicles. As the application fields of lithium secondary batteries diversify, the required physical property conditions are gradually increasing, and specifically, it is necessary to develop lithium secondary batteries that can operate stably even under high temperature conditions and have long life characteristics.

[0005] When a lithium secondary battery is operated under high temperature conditions, PF6 is decomposed from a lithium salt (such as LiPF6) contained in an electrolyte solution. - The reaction of the anion can be intensified, thereby generating a Lewis acid (such as PF5), which reacts with moisture to generate HF. The decomposition products (such as PF5 and HF) can not only destroy the film formed on the electrode surface, but also cause a decomposition reaction of the organic solvent, and can react with the decomposition product of the positive electrode active material to dissolve the transition metal ions, and the dissolved transition metal ions can be electrodeposited on the negative electrode to destroy the film formed on the negative electrode surface.

[0006] If the above-mentioned electrolyte decomposition reaction continues on the damaged membrane, the performance of the battery will further decrease, so it is necessary to develop a secondary battery that can maintain excellent performance even under high temperature conditions. Summary of the invention

[0007] [Technical issues]

[0008] One aspect of the present invention provides a nonaqueous electrolyte solution that facilitates formation of a reinforced film on an electrode, and a lithium secondary battery including the nonaqueous electrolyte solution.

[0009] [Technical solution]

[0010] According to one aspect of the present invention, a non-aqueous electrolyte solution for a lithium secondary battery is provided, which includes: a lithium salt; an organic solvent; and a compound represented by Formula 1.

[0011] [Formula 1]

[0012]

[0013] In formula 1,

[0014] R1 is a halogen group,

[0015] R2 and R3 are each independently an alkyl group having 1 to 10 carbon atoms,

[0016] p is any integer from 1 to 5,

[0017] q is any integer from 0 to 5-p,

[0018] r is any integer from 0 to 4, and

[0019] m is any integer from 1 to 5-r.

[0020] According to another aspect of the present invention, a lithium secondary battery is provided, comprising: a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; a separator disposed between the positive electrode and the negative electrode; and the above-mentioned nonaqueous electrolyte solution for lithium secondary batteries.

[0021] [Beneficial Effects]

[0022] The nonaqueous electrolyte solution of the present invention has the effect of forming a thin and strong film on an electrode due to the inclusion of a pyridine compound substituted with a halogenated benzene, and thus it can ultimately provide a lithium secondary battery having improved electrochemical properties even under high-temperature storage conditions. DETAILED DESCRIPTION

[0023] Hereinafter, the present invention will be described in more detail.

[0024] Generally, lithium salts, such as LiPF6, which is widely used in lithium secondary battery electrolyte solutions, contain anions that form decomposition products such as hydrogen fluoride (HF) and PF5 due to thermal decomposition or moisture. These decomposition products are acidic and deteriorate the membrane or electrode surface in the battery.

[0025] Due to the decomposition products of the electrolyte solution and the change in the structure of the positive electrode caused by repeated charging and discharging, the transition metal in the positive electrode is easily dissolved into the electrolyte solution, and the dissolved transition metal is redeposited on the positive electrode to increase the resistance of the positive electrode. In addition, in the case where the dissolved transition metal moves to the negative electrode through the electrolyte solution, the dissolved transition metal is electrodeposited on the negative electrode to cause the destruction of the solid electrolyte interphase (SEI) film and additional electrolyte decomposition reaction, and as a result, problems such as lithium ion consumption and resistance increase occur.

[0026] In addition, during the initial activation of the battery, a protective film is formed on the positive and negative electrodes by the reaction of the electrolyte solution, wherein, in the case where the film becomes unstable due to the above reasons, additional decomposition of the electrolyte solution occurs during charge-discharge or high temperature exposure, thereby promoting battery degradation and generating gas.

[0027] In order to solve these problems, the inventors included the compound represented by Formula 1 in a non-aqueous electrolyte solution, and thus found that the decomposition reaction of the electrolyte solution can be reduced and the dissolution and gas generation of transition metals can be suppressed. Specifically, since the compound represented by Formula 1 includes a pyridine group, it decomposes rapidly in the negative electrode to form a thin and strong SEI film on the electrode, so when it is used in a battery, it has the effect of improving the initial resistance. In particular, since the pyridine group is substituted with halogenated benzene, especially fluorobenzene, a LiF film can be formed by providing a fluorine (F) component, so it has the effect of suppressing the degradation of the negative electrode during battery operation, and ultimately has the effect of reducing the amount of gas generated and the rate of increase in resistance under high temperature storage conditions.

[0028] In the case of using silicon-based materials as negative electrode active materials, there is a problem of difficulty in film formation due to its low electronic conductivity, and since the compound represented by Formula 1 can react quickly, this problem can be compensated. In addition, in the case of introducing high nickel (high Ni) active materials as positive electrode active materials, due to structural instability, it increases side reactions and gas generation, so it can be a factor that reduces battery life. Since the compound represented by Formula 1 has an excellent effect of improving the film properties of the electrode, it can solve the problems caused by the use of high nickel positive electrode active materials.

[0029] Hereinafter, each component constituting the present invention will be described in more detail.

[0030] Non-aqueous electrolyte solution

[0031] The present invention provides a non-aqueous electrolyte solution for a lithium secondary battery, comprising: a lithium salt; an organic solvent; and a compound represented by Formula 1.

[0032] Hereinafter, each component will be described in detail.

[0033] (1) Compound represented by formula 1

[0034] The nonaqueous electrolyte solution of the present invention includes a compound represented by Formula 1 below.

[0035] [Formula 1]

[0036]

[0037] In formula 1,

[0038] R1 is a halogen group,

[0039] R2 and R3 are each independently an alkyl group having 1 to 10 carbon atoms,

[0040] p is any integer from 1 to 5,

[0041] q is any integer from 0 to 5-p,

[0042] r is any integer from 0 to 4, and

[0043] m is any integer from 1 to 5-r.

[0044] In an embodiment of the present invention, R1 in Formula 1 may be fluorine. In this case, there is an effect of forming a film having a LiF component on the negative electrode by removing fluorine (F).

[0045] R2 and R3 may be hydrogen or an alkyl group having 1 to 5 carbon atoms, preferably hydrogen or an alkyl group having 1 to 3 carbon atoms, more preferably hydrogen or methyl.

[0046] In an embodiment of the present invention, p may be 1 or 2, preferably 1.

[0047] In an embodiment of the present invention, q and r may each be 0 or 1, and preferably, one of them is 0 and the other is 1, or both may be 0. In addition, m may be 1 or 2, preferably 1.

[0048] In an embodiment of the present invention, the compound represented by Formula 1 may be represented by Formula 1-1. As described above, when the 4-position of the pyridine ring (ie, the para position of the nitrogen atom) is substituted with a halogenated benzene, since no steric hindrance is generated at the nitrogen (N) portion of pyridine, it is easy to react with the negative electrode, which is more ideal.

[0049] [Formula 1-1]

[0050]

[0051] In Formula 1-1, R1 to R3, p, q and r are as defined in Formula 1.

[0052] In an embodiment of the present invention, Formula 1 may be represented by the following Formula 1A.

[0053] [Formula 1A]

[0054]

[0055] [Formula 1B]

[0056]

[0057] [Formula 1C]

[0058]

[0059] In an embodiment of the present invention, the amount of the compound represented by Formula 1 may be 0.1 wt % to 5 wt %, preferably 0.1 wt % to 1 wt %, and more preferably 0.1 wt % to 0.5 wt %, based on the total weight of the nonaqueous electrolyte solution.

[0060] When the amount of the compound represented by Formula 1 is 0.1 wt % or more, the above effect can be fully achieved by forming a film on the negative electrode, and when the amount is 5 wt % or less, the decrease in ion conductivity due to the increase in viscosity of the electrolyte solution is prevented, which is more ideal.

[0061] (2) Additives

[0062] In order to prevent the electrolyte solution from decomposing in a high voltage environment and causing electrode collapse, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge protection and battery expansion inhibition effect at high temperatures, the non-aqueous electrolyte solution of the present invention may optionally further include the following additives if necessary.

[0063] The additive may be at least one selected from the group consisting of cyclic carbonate compounds, sultone compounds, sulfate compounds, phosphorus compounds, nitrile compounds, amine compounds, silane compounds, benzene compounds and lithium salt compounds.

[0064] The cyclic carbonate-based compound may be at least one selected from vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and fluoroethylene carbonate (FEC), and may specifically be vinylene carbonate.

[0065] The sultone compound is a material that can form a stable SEI film on the surface of the negative electrode through a reduction reaction, wherein the sultone compound can be at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethylene sultone, 1,3-propylene sultone (PRS), 1,4-butene sultone and 1-methyl-1,3-propylene sultone, and can specifically be 1,3-propane sultone (PS).

[0066] The sulfate / ester compound is a material that can undergo electrolysis on the surface of the negative electrode to form a stable SEI film that does not break even during high-temperature storage, wherein the sulfate / ester compound can be at least one of ethylene sulfate (ESA), trimethylene sulfate (TMS) or methyl trimethylene sulfate (MTMS).

[0067] The phosphorus compound may be a phosphate or phosphite compound, and specifically, may be at least one selected from the group consisting of tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate and tris(trifluoroethyl)phosphite.

[0068] The nitrile compound may be at least one selected from the group consisting of succinonitrile (SN), adiponitrile (ADN), acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanecarbonitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzylacetonitrile, 2-fluorobenzeneacetonitrile, 4-fluorobenzeneacetonitrile, ethylene glycol bis(2-cyanoethyl) ether (ASA3), 1,3,6-hexanetricarboxylate (HTCN), 1,4-dicyano-2-butene (DCB) and 1,2,3-tris(2-cyanoethyl)propane (TCEP).

[0069] The amine compound may be at least one of triethanolamine and ethylenediamine, and the silane compound may be tetravinylsilane.

[0070] The benzene compound may be at least one selected from the group consisting of monofluorobenzene, difluorobenzene, trifluorobenzene, and tetrafluorobenzene.

[0071] The lithium salt compound is a compound different from the lithium salt contained in the non-aqueous electrolyte solution, wherein the lithium salt compound can be at least one compound selected from the group consisting of lithium difluorophosphate (LiDFP; LiPO2F2), lithium bis(oxalate)borate (LiBOB; LiB(C2O4)2), lithium tetrafluoroborate (LiBF4), lithium tetraphenylborate and lithium difluorobis(oxalate)phosphate (LiDFOP).

[0072] Preferably, the non-aqueous electrolyte solution of the embodiment of the present invention may further include at least one additive selected from the group consisting of vinylene carbonate (VC), 1,3-propane sultone (PS), ethylene sulfate (ESa) and lithium difluorophosphate (LiDFP), and may more preferably include vinyl ethylene carbonate (VEC). In this case, the advantage is that the negative electrode film can be strengthened and the resistance can be further improved.

[0073] The amount of the additive may be 0.1 wt % to 10 wt %, preferably 0.3 wt % to 5 wt % based on the total weight of the nonaqueous electrolyte solution. When the amount of the additive is within the above range, there is an effect of suppressing side reactions by forming a film on the positive electrode and the negative electrode.

[0074] (3) Organic solvents

[0075] The nonaqueous electrolyte solution of the present invention includes an organic solvent.

[0076] The various organic solvents that are usually used in lithium electrolytes can be used as organic solvents without restriction. For example, the organic solvent can be a cyclic carbonate solvent, a linear carbonate solvent, a linear ester solvent, a cyclic ester solvent, a nitrile solvent or a mixture thereof, can preferably include at least two kinds of mixtures selected from the group consisting of a cyclic carbonate solvent, a linear carbonate solvent and a linear ester solvent, and can more preferably include a mixture of a cyclic carbonate solvent and a linear carbonate solvent.

[0077] The cyclic carbonate organic solvent is a high-viscosity organic solvent, which can well dissociate the lithium salt in the electrolyte due to its high dielectric constant, and can be at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate and vinylene carbonate, and preferably may include ethylene carbonate (EC) or propylene carbonate (PC).

[0078] In addition, the chain carbonate compound is an organic solvent with low viscosity and low dielectric constant, which can be at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate, and can preferably include ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or diethyl carbonate (DEC).

[0079] In order to prepare an electrolyte solution having high ion conductivity, it is preferred to use a mixture of a cyclic carbonate-based solvent and a chain carbonate-based solvent as the organic solvent.

[0080] The chain ester solvent may be at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate, and may preferably be methyl propionate, ethyl propionate, or propyl propionate.

[0081] The cyclic ester solvent may be at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.

[0082] The nitrile solvent may be at least one selected from the group consisting of succinonitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanecarbonitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorophenyl cyanide and 4-fluorophenyl cyanide, and may preferably be succinonitrile.

[0083] Unless otherwise specified, the remainder of other components except the organic solvent in the total weight of the nonaqueous electrolyte solution, such as the amount of the compound represented by Formula 1, additives, and lithium salt, may all be the organic solvent.

[0084] (4) Lithium salt

[0085] The nonaqueous electrolyte solution of the present invention includes a lithium salt.

[0086] Any lithium salt generally used in an electrolyte solution for a lithium secondary battery may be used as the lithium salt without limitation, and specifically, the lithium salt may include Li + as a cation, and may include a - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - , B 10 Cl 10 - 、AlCl4 - 、AlO2 - PF6 - CF3SO3 - 、CH3CO2 - CF3CO2 - 、AsF6 - 、SbF6 - 、CH3SO3 - 、(CF3CF2SO2)2N - 、(CF3SO2)2N - 、(FSO2)2N - 、BF2C2O4 - , BC4O8 - 、BF2C2O4CHF - PF4C2O4 - PF2C4O8 - PO2F2 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF- 、(CF3)6P - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - CF3(CF2)7SO3 - and SCN - as an anion.

[0087] Specifically, the lithium salt may be at least one selected from the group consisting of LiPF6, LiClO4, LiBF4, lithium bis(fluorosulfonyl)imide (LiN(FSO2)2; LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(pentafluoroethanesulfonyl)imide (LiBETI), lithium trifluoromethanesulfonate (LiSO3CF3), lithium difluorophosphate (LiPO2F2), lithium bis(oxalate)borate (LiBOB), lithium difluoro(oxalate)borate (LiFOB), lithium difluoro(bisoxalate)phosphate (LiDFOP), lithium tetrafluoro(oxalate)phosphate (LiTFOP) and lithium fluoromalonate (difluoro)borate (LiFMDFB), and may preferably be LiPF6.

[0088] In an embodiment of the present invention, the concentration of the lithium salt in the non-aqueous organic solution containing the lithium salt and the organic solvent may be 0.5 M to 4.0 M, particularly 0.5 M to 3.0 M, and more particularly 0.8 M to 2.0 M. When the concentration of the lithium salt is within the above range, sufficient electrolyte impregnation can be obtained by preventing excessive increases in viscosity and surface tension, while sufficiently ensuring the effects of improving low-temperature output and improving cycle characteristics.

[0089] Lithium secondary battery

[0090] Next, the lithium secondary battery of the present invention will be described.

[0091] The lithium secondary battery of the present invention includes a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, a separator disposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte solution. In this case, the non-aqueous electrolyte solution is the above-mentioned non-aqueous electrolyte solution of the present invention. Since the non-aqueous electrolyte solution has been described above, its description will be omitted and other components will be described below.

[0092] (1) Positive electrode

[0093] The positive electrode of the present invention includes a positive electrode active material, and may be prepared by coating a positive electrode collector with a positive electrode slurry including the positive electrode active material, a binder, a conductive agent, and a solvent, and then drying and roll-pressing the coated positive electrode collector.

[0094] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used.

[0095] The positive electrode active material is a compound capable of reversibly intercalating and deintercalating lithium, and the positive electrode active material may be at least one selected from the group consisting of LCO (LiCoO2), LNO (LiNiO2), LMO (LiMnO2), LiMn2O4, LiCoPO4, LFP (LiFePO4), and lithium composite transition metal oxides containing nickel (Ni), cobalt (Co), and manganese (Mn).

[0096] The molar ratio of nickel in the transition metal of the positive electrode active material can be 70 mol% or more, preferably 80 mol% or more, more preferably 90 mol% or more. That is, even in a battery containing a ultra-high nickel positive electrode active material with a nickel molar ratio of 90 mol% or more, excellent resistance characteristics and gas generation amount can be obtained when using the non-aqueous electrolyte solution of the present invention.

[0097] In an embodiment of the present invention, the lithium composite transition metal oxide may be a compound represented by the following formula 2. That is, the positive electrode active material of the embodiment of the present invention may include the lithium composite transition metal oxide represented by the following formula 2.

[0098] [Formula 2]

[0099] Li 1+x (Ni a Co b Mn c M d )O2

[0100] In formula 2, M is at least one selected from the group consisting of tungsten (W), copper (Cu), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), zirconium (Zr), zinc (Zn), aluminum (Al), indium (In), tantalum (Ta), yttrium (Y), lanthanum (La), strontium (Sr), gallium (Ga), scandium (Sc), gadolinium (Gd), samarium (Sm), calcium (Ca), cerium (Ce), niobium (Nb), magnesium (Mg), boron (B), and molybdenum (Mo),

[0101] 1 + x, a, b, c, and d are atomic fractions of each independent element,

[0102] wherein, -0.2 ≤ x ≤ 0.2, 0.6 ≤ a < 1, 0 < b ≤ 0.3, 0 < c ≤ 0.3, 0 ≤ d ≤ 0.1, and a + b + c + d = 1.

[0103] 1 + x represents the molar ratio of lithium in the lithium composite transition metal oxide, where x can satisfy -0.1 ≤ x ≤ 0.2 or 0 ≤ x ≤ 0.2. When the molar ratio of lithium satisfies the above range, the crystal structure of the lithium composite transition metal oxide can be formed stably.

[0104] a represents the molar ratio of nickel in all metals other than lithium in the lithium composite transition metal oxide, where a can satisfy 0.70 ≤ a < 1, 0.80 ≤ a < 1, 0.85 ≤ a < 1 or 0.90 ≤ a < 1. When the molar ratio of nickel satisfies the above range, high capacity can be achieved because high energy density can be exhibited.

[0105] b represents the molar ratio of cobalt in all metals other than lithium in the lithium composite transition metal oxide, where b can satisfy 0 < b ≤ 0.25, 0 < b ≤ 0.20, 0 < b ≤ 0.15 or 0 < b ≤ 0.10. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be achieved.

[0106] c represents the molar ratio of manganese in all metals other than lithium in the lithium composite transition metal oxide, where c can satisfy 0 < c ≤ 0.25, 0 < c ≤ 0.20, 0 < c ≤ 0.15 or 0 < c ≤ 0.10. When the molar ratio of manganese satisfies the above range, the structural stability of the positive electrode active material is excellent.

[0107] In an embodiment of the present invention, the lithium composite transition metal oxide may include at least one doping element selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and may preferably include Al as the doping element. In other words, d representing the molar ratio of the doping element in all metals other than lithium in the lithium composite transition metal oxide can satisfy 0 < d ≤ 0.10, 0 < d ≤ 0.08, 0 < d ≤ 0.05 or 0 < d ≤ 0.03.

[0108] Preferably, a, b, c, and d in Formula 2 can satisfy 0.70 ≤ a < 1, 0 < b ≤ 0.2, 0 < c ≤ 0.2, and 0 ≤ d ≤ 0.1 respectively, and more preferably, 0.80 ≤ a < 1, 0 < b ≤ 0.15, 0 < c ≤ 0.15, and 0 ≤ d ≤ 0.05.

[0109] Based on the total weight of the solid components in the positive electrode paste, the content of the positive electrode active material can be 80% by weight to 99% by weight, specifically 90% by weight to 99% by weight. When the amount of the positive electrode active material is 80% by weight or less, the capacity may decrease due to the reduction in energy density.

[0110] The binder is a component that helps the bonding between the active material and the conductive agent and the bonding with the current collector, wherein the binder can be added in an amount of 1 wt % to 30 wt % based on the total weight of the solid components in the positive electrode slurry. Examples of the binder can be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0111] In addition, the conductive agent is a material that provides conductivity without causing adverse chemical changes in the battery, and may be added in an amount of 0.5 wt % to 20 wt % based on the total weight of solid components in the positive electrode slurry.

[0112] The conductive agent can be selected from the following conductive materials, for example: carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black; graphite powder, such as natural graphite, artificial graphite, carbon nanotubes and graphite; conductive fibers, such as carbon fibers and metal fibers; conductive powders, such as fluorocarbon powders, nickel powders and aluminum powders; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives.

[0113] In addition, the solvent of the positive electrode slurry may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and its amount may be such that the desired viscosity is obtained when the positive electrode active material, the binder and the conductive agent are included. For example, the content of the solvent may be such that the concentration of the solid components in the positive electrode slurry containing the positive electrode active material, the binder and the conductive agent is 40 wt % to 90 wt %, preferably 50 wt % to 80 wt %.

[0114] (2) Negative electrode

[0115] The negative electrode of the present invention includes a negative electrode active material, and may be prepared by coating a negative electrode collector with a negative electrode slurry including the negative electrode active material, a binder, a conductive agent, and a solvent, and then drying and roll-pressing the coated negative electrode collector.

[0116] The negative electrode current collector generally has a thickness of 3 μm to 500 μm. The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause adverse chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloy can be used. In addition, similar to the positive electrode current collector, the negative electrode current collector may have a fine surface roughness to improve the adhesion of the negative electrode active material. The negative electrode current collector can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0117] In an embodiment of the present invention, the negative electrode active material may include a silicon-based material, and the silicon-based material is selected from the group consisting of Si, SiO x (0 < x < 2) and Si-Y alloys (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and cannot be Si), and is preferably SiO.

[0118] Since the capacity of the silicon-based negative electrode active material is nearly 10 times that of graphite, the fast charging performance of the battery can be improved by reducing the mass loading (mg·cm -2 ). However, the disadvantage of the negative electrode containing the silicon-based negative electrode active material is that, due to its lower conductivity than that of the graphite negative electrode, it is difficult to form a film on the negative electrode. Among them, since the non-aqueous electrolyte solution of the present invention contains the compound represented by Formula 1, it decomposes rapidly at the negative electrode due to the pyridine structure, thereby forming a thin and strong SEI film on the negative electrode. Therefore, it can effectively compensate for the above disadvantages.

[0119] In an embodiment of the present invention, based on the total weight of the negative electrode active material, the content of the silicon-based material may be 1 wt% to 20 wt%, preferably 5 wt% to 15 wt%. When the silicon-based material is within the above range, there is an effect of increasing the negative electrode capacity and improving the fast charging performance.

[0120] In addition, in addition to the silicon-based material, the negative electrode active material may include at least one selected from the following materials: a carbon material capable of reversibly inserting / extracting lithium ions; a metal or an alloy of lithium and the metal; a metal composite oxide; a material that can be doped and de-doped with lithium; lithium metal; and a transition metal oxide.

[0121] As the carbon material capable of reversibly inserting / extracting lithium ions, the carbon-based negative electrode active material commonly used in lithium ion secondary batteries can be used without particular limitation, and as typical examples, crystalline carbon and / or amorphous carbon can be used. Examples of crystalline carbon can be graphite, such as natural graphite or artificial graphite that is irregular, planar, flaky, spherical, or fibrous, and examples of amorphous carbon can be soft carbon (low-temperature sintered carbon), hard carbon, mesophase pitch carbide, and calcined coke.

[0122] As the metal or the alloy of lithium and the metal, a metal selected from the group consisting of copper (Cu), nickel (Ni), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), silicon (Si), antimony (Sb), lead (Pb), indium (In), zinc (Zn), barium (Ba), radium (Ra), germanium (Ge), aluminum (Al), and tin (Sn), or an alloy of lithium and the metal can be used.

[0123] As the metal composite oxide, at least one selected from the group consisting of PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3(0 ≤ x ≤ 1), Li x WO2(0 ≤ x ≤ 1) and Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb or Ge; Me': Al, B, P, Si, elements of Groups 1, 2 and 3 in the periodic table or halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8).

[0124] The materials that can be doped and undoped with lithium can include Sn, SnO2 and Sn - Y (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, and is not Sn), and a mixture of SiO2 and at least one of them can also be used.

[0125] In Si - Y and Sn - Y, the element Y can be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po and combinations thereof.

[0126] Examples of the transition metal oxide can be lithium - containing titanium composite oxide (LTO), vanadium oxide and lithium vanadium oxide.

[0127] In an embodiment of the present invention, the negative electrode active material can be a mixture of a carbon - based material and a silicon - based material, and preferably can be a mixture of graphite and SiO.

[0128] Based on the total weight of the solid components in the negative electrode slurry, the content of the negative electrode active material can be 80% by weight to 99% by weight.

[0129] The binder is a component that helps the bonding between the conductive agent, the active material and the current collector, wherein the binder is generally added in an amount of 1 wt % to 30 wt % based on the total weight of the solid components in the negative electrode slurry. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber and various copolymers thereof.

[0130] The conductive agent is a component for further improving the conductivity of the negative electrode active material, wherein the conductive agent can be added in an amount of 0.5 wt % to 20 wt % based on the total weight of the solid components in the negative electrode slurry. Any conductive agent can be used without particular limitation, as long as it has conductivity and does not cause adverse chemical changes in the battery, for example, conductive materials that can be used include: carbon black, such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powder, such as natural graphite with a well-developed crystal structure, artificial graphite, carbon nanotubes, or graphite; conductive fibers, such as carbon fibers and metal fibers; conductive powders, such as fluorocarbon powders, aluminum powders, and nickel powders; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0131] The solvent of the negative electrode slurry may include water or an organic solvent, such as NMP and alcohol, and its amount may be such that the desired viscosity is obtained when the negative electrode active material, the binder and the conductive agent are included. For example, the content of the solvent may be such that the concentration of the solid component in the slurry containing the negative electrode active material, the binder and the conductive agent is 30 wt % to 80 wt %, preferably 40 wt % to 70 wt %.

[0132] (3) Diaphragm

[0133] The lithium secondary battery of the present invention includes a separator between a positive electrode and a negative electrode.

[0134] The separator separates the negative electrode and the positive electrode and provides a movement path for lithium ions, wherein any separator can be used as the separator without particular limitation as long as it is commonly used in lithium secondary batteries, and in particular, a separator having high moisture retention ability and excellent safety for the electrolyte and low resistance to the transmission of electrolyte ions can be used.

[0135] Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure with more than two layers of the above-mentioned polymer can be used. Moreover, a common porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated diaphragm including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a diaphragm with a single layer or multilayer structure can be selectively used.

[0136] The lithium secondary battery of the present invention as described above can be applied to portable devices such as mobile phones, notebook computers, and digital cameras; and electric vehicles such as hybrid electric vehicles (HEVs).

[0137] Therefore, according to another embodiment of the present invention, a battery module including the lithium secondary battery as a unit cell and a battery pack including the battery module are provided.

[0138] The battery module or battery pack may be used as a power source for at least one of the following medium and large-sized devices: a power tool; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0139] The shape of the lithium secondary battery of the present invention is not particularly limited, and a cylindrical shape using a can, a prismatic shape, a pouch shape, or a coin shape may be used.

[0140] The lithium secondary battery of the present invention can be used not only in a single battery used as a power source for small devices but also as a unit cell in a medium or large battery module including a plurality of single batteries.

[0141] Hereinafter, the present invention will be described in detail according to specific embodiments.

[0142] <Example: Preparation of lithium secondary battery>

[0143] Example 1

[0144] 1) Preparation of non-aqueous electrolyte solution

[0145] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:70, and then LiPF6 was dissolved so that the concentration of LiPF6 was 1 M, thereby preparing a non-aqueous organic solution. 0.1 wt % of the compound represented by Formula 1A, 0.5 wt % of vinylene carbonate (VC) and the remaining amount of the non-aqueous organic solution were mixed to prepare a 100 wt % non-aqueous electrolyte solution.

[0146] 2) Preparation of lithium secondary batteries

[0147] As the positive electrode active material, Li(Ni 0.9 Mn 0.03 Co 0.06 Al 0.01 )O2, a conductive agent (carbon black) and a binder (polyvinylidene fluoride) were added to N-methyl-2-pyrrolidone (NMP) at a weight ratio of 97.6:0.8:1.6 to prepare a positive electrode slurry (solid content: 60 wt%). A 13.5 μm thick aluminum (Al) film as a positive electrode current collector was coated with the positive electrode slurry, dried and then roll-pressed to prepare a positive electrode.

[0148] The negative electrode active material (graphite: SiO = 90.0: 10.0 weight ratio), binder (SBR-CMC) and conductive agent (carbon black) were added to water as a solvent at a weight ratio of 97.6: 0.8: 1.6 to prepare a negative electrode slurry (solid content: 60 weight %). A 6 μm thick copper (Cu) film as a negative electrode current collector was coated with the negative electrode slurry, dried and then rolled to prepare a negative electrode. The positive electrode, the polyolefin-based porous separator coated with inorganic particles (Al2O3) and the negative electrode were stacked in sequence to prepare an electrode assembly.

[0149] The prepared electrode assembly was housed in a cylindrical battery case, and the nonaqueous electrolyte solution prepared above was injected therein to prepare a lithium secondary battery.

[0150] Example 2

[0151] A lithium secondary battery was prepared in the same manner as in Example 1, except that the amount of the compound represented by Formula 1A was changed to 0.3 wt % during the preparation of the nonaqueous electrolyte solution.

[0152] Example 3

[0153] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1B was used instead of the compound represented by Formula 1A during the preparation of the nonaqueous electrolyte solution.

[0154] Example 4

[0155] A lithium secondary battery was prepared in the same manner as in Example 3, except that the amount of the compound represented by Formula 1B was changed to 0.3 wt % during the preparation of the nonaqueous electrolyte solution.

[0156] Example 5

[0157] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1C was used instead of the compound represented by Formula 1A during the preparation of the nonaqueous electrolyte solution.

[0158] Example 6

[0159] A lithium secondary battery was prepared in the same manner as in Example 5, except that the amount of the compound represented by Formula 1C was changed to 0.3 wt % during the preparation of the nonaqueous electrolyte solution.

[0160] Comparative Example 1

[0161] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1A was not added during the preparation of the nonaqueous electrolyte solution.

[0162] Comparative Example 2

[0163] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1A was replaced with a compound represented by the following Formula Z1 in the preparation of the nonaqueous electrolyte solution.

[0164] [Formula Z1]

[0165]

[0166] Comparative Example 3

[0167] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1A was replaced with a compound represented by the following Formula Z2 in the preparation of the nonaqueous electrolyte solution.

[0168] [Formula Z2]

[0169]

[0170] Comparative Example 4

[0171] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1A was replaced with a compound represented by the following Formula Z3 during the preparation of the nonaqueous electrolyte solution.

[0172] [Formula Z3]

[0173]

[0174] Comparative Example 5

[0175] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1A was replaced with a compound represented by the following Formula Z4 during the preparation of the nonaqueous electrolyte solution.

[0176] [Formula Z4]

[0177]

[0178] <Experimental Example: Battery Performance Evaluation>

[0179] Experimental Example 1. Measurement of initial resistance

[0180] After the formation process of the lithium secondary batteries prepared in the embodiments and comparative examples, the lithium secondary batteries were charged by constant current / constant voltage (CC / CV) (0.05C cut-off) to 4.2V at a rate of 0.33C at 25°C, and discharged by constant current (CC) to 2.80V at a rate of 0.33C, and then the initial resistance was measured. The results are shown in Table 1 below.

[0181] Experimental Example 2: Measurement of resistance increase rate after high temperature storage

[0182] Each battery that had completed the initial evaluation of Experimental Example 1 was fully charged to 100% of the state of charge (SOC) under the same conditions and stored at high temperature (60° C.) for 4 weeks. Thereafter, after each battery was transferred to a charger and discharger at room temperature (25° C.), the resistance was measured again, the resistance increase rate was calculated by the following equation 1, and the results are presented in the following Table 1.

[0183] Equation 1: Resistance increase rate (%) = {(resistance after high temperature storage - initial resistance) / initial resistance} × 100

[0184] Experimental Example 3. Measurement of gas generation after high temperature storage

[0185] After the formation process of the lithium secondary batteries prepared in the embodiments and comparative examples, the lithium secondary batteries were charged to 4.2V (0.05C cutoff) at a rate of 0.33C under constant current / constant voltage conditions at 25°C, so that the lithium secondary batteries were fully charged to 100% SOC. After the fully charged batteries were stored at 60°C for 4 weeks, the gas generation was measured at room temperature (25°C) using a buoyancy measurement method. When the gas generation measured in Comparative Example 1 was set to 100%, the relative gas generation of each battery was calculated and shown in Table 1 below.

[0186] [Table 1]

[0187]

[0188] According to the results of Table 1, it can be confirmed that the nonaqueous electrolyte solution including the compound represented by Formula 1 effectively improves the resistance increase rate and the gas generation amount after high-temperature storage.

[0189] Specifically, it can be confirmed that the batteries of Examples 1 to 6 have better resistance increase rate and gas generation after high temperature storage than Comparative Example 2 (using a compound represented by Formula Z1 in which pyridine is substituted instead of fluorobenzene), Comparative Example 3 (using a compound represented by Formula Z2 in which unsubstituted benzene is substituted instead of fluorobenzene), Comparative Example 4 (using a compound represented by Formula Z3 fluorobenzene), and Comparative Example 4 (using a compound represented by Formula Z4 fluoropyridine). In particular, relative to Comparative Examples 2 and 3, since a compound not containing F is used, LiF is not formed on the negative electrode, it can be confirmed that the resistance increase rate after high temperature storage is not as good as that of Comparative Example 1.

[0190] Even if the nonaqueous electrolyte solution contains the compound represented by Formula 1, when the amount thereof is 0.3 wt % or more based on the total weight of the nonaqueous electrolyte solution, it can be confirmed that the effect of improving the resistance increase rate and gas generation amount after high-temperature storage is more excellent.

Claims

1. A non-aqueous electrolyte solution for a lithium secondary battery, comprising: a lithium salt; an organic solvent; and a compound represented by Formula 1; [Formula 1] In Formula 1, R1 is a halogen group, R2 and R3 are each independently an alkyl group having 1 to 10 carbon atoms, p is any integer from 1 to 5, q is any integer from 0 to 5 - p, r is any integer from 0 to 4, and m is any integer from 1 to 5 - r.

2. The non-aqueous electrolyte solution for a lithium secondary battery according to claim 1, wherein R1 is fluorine.

3. The non-aqueous electrolyte solution for a lithium secondary battery according to claim 1, wherein q and r are each 0.

4. The non-aqueous electrolyte solution for a lithium secondary battery according to claim 1, wherein the compound represented by Formula 1 is represented by Formula 1-1: [Formula 1-1] In Formula 1-1, R1 to R3, p, q and r are as defined in Formula 1.

5. The non-aqueous electrolyte solution for lithium secondary battery according to claim 1, wherein Based on the total weight of the non-aqueous electrolyte solution, the amount of the compound represented by Formula 1 is 0.05 wt% to 5 wt%.

6. The non-aqueous electrolyte solution for lithium secondary battery according to claim 1, wherein Based on the total weight of the non-aqueous electrolyte solution, the amount of the compound represented by Formula 1 is 0.1 wt% to 1 wt%.

7. The non-aqueous electrolyte solution for a lithium secondary battery according to claim 1, further comprising at least one additive selected from the group consisting of vinylene carbonate, 1,3 - propane sultone, ethylene sulfite and lithium difluorophosphate.

8. The non-aqueous electrolyte solution for lithium secondary battery according to claim 1, wherein The organic solvent includes a mixture of a cyclic carbonate solvent and a linear carbonate solvent.

9. A lithium secondary battery, comprising: a positive electrode comprising a positive electrode active material; a negative electrode comprising a negative electrode active material; a separator disposed between the positive electrode and the negative electrode; and the non-aqueous electrolyte solution according to claim 1.

10. The lithium secondary battery according to claim 9, wherein: The positive electrode active material comprises a lithium composite transition metal oxide represented by Formula 2: [Formula 2] Li 1+x (Ni a Co b Mr c M d )O2 In Formula 2, M is at least one selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, 1 + x, a, b, c and d are atomic fractions of respective independent elements, where -0.2 ≤ x ≤ 0.2, 0.6 ≤ a < 1, 0 < b ≤ 0.3, 0 < c ≤ 0.3, 0 ≤ d ≤ 0.1, and a + b + c + d = 1.

11. The lithium secondary battery according to claim 10, wherein: a, b, c and d in Formula 2 respectively satisfy 0.80 ≤ a < 1, 0 < b ≤ 0.15, 0 < c ≤ 0.15 and 0 ≤ d ≤ 0.

05.

12. The lithium secondary battery according to claim 9, wherein: The negative electrode active material comprises a silicon-based material.

Citation Information

Patent Citations

  • Encapsulating composition and Organic electronic device comprising the same

    KR1020220098826A

  • The functional finger prosthetic

    KR1020230090520A